Sistema informático para la gestión de contratos y desempeño de docentes para la Dirección de Evaluación, Acreditación y Aseguramiento de la Calidad de la Educación de la Universidad Técnica de Babahoyo. - Vera Vargas, Doris Marian (2017)
The present project describes the development and use of the Computer System for contract management and teacher performance, carried out for the Directorate of Evaluation, Accreditation and Quality Assurance of Education of the Technical University of Babahoyo. System that allows to manage the information, where the hardware, software and computer personnel are interrelated. The problems that arise for the realization of the computer system are due to several disadvantages such as: duplicity of information, lack of documents, wrong data and wasted time. The inclination to solve the problematic is so that the direction has good results of availability, agility and truthful information, when they require it; in addition, to encourage the creation of more useful computer systems for the same direction or for other departments of the Technical University of Babahoyo. This project is divided into three chapters. The first chapter is to diagnose needs and requirements, describes in detail the area of ​​influence in which the prototype will be executed, important aspects, requirements, reasons for the elaboration of the same, the direct and indirect beneficiaries of the prototype are detailed and the way in which it contributes to the satisfaction of their needs. The second chapter is the development of the prototype, here the prototype is defined with the requirements, the main functions to be fulfilled by the users, the theory that supports the prototype, its objectives, the optimal solution of the application with physical and logical resources, detail of the activities developed for the elaboration of the prototype.